Chemical composition, in vitro dry matter digestibility, total phenolics and proanthocynidins in bedge lucerne (JJesmenthus virgatus) exotic germplasm - SINGH, SULTAN; NEGI, ARVIND SINGH; AGARWAL, D K; KATIYAR, P K; SINGH, U P (The Indian Journal of Animal Sciences, 2014)
Eighteen genotypes (IL 97-239, -224,-226, -227, -228, -230, -267, -253, -254, -271, -273, -217, -218, -251, -231, -242, -243 and IL 97-257) from exotic germplasm of hedge lucerne grown under uniform agronomic and soil conditions were collected at 50% flowering and evaluated for various nutritional traits. CP contents varied (15.4 to 26.75%) significantly (P<0.05) amongst the genotypes. The mean CP content of the germplasm was 20.62%. The cell wall contents (NDF, ADF and cellulose) varied significantly (P<0.05) in the evaluated germplasm. The average NDF and ADF contents were 42.31 and 34.94%, respectively, in the tested genotypes. Gennplasm exhibited 20.58% mean lignin concentration. IL 97-217 and IL 97-267 lines contained minimum (11.54) and maximum (26.44%) lignin concentration respectively. Genotypes showed significant variability (P<0.05) in total phenolics and total proanthocyanidins (PA) concentration. In the gennplasm proportion of mean extractable PA, protein bound PA and fibre bound PA were 2.91,0.44 and 0.36% respectively. The mean IVDMD of evaluated germplasm was 50.96% and IL 97-254, IL 97-217, IL 97-239 and IL 97-242 genotypes revealed the maximum (64.07,64.63) and minimum (38.68, 38.00%) respectively. The results showed that genotypes IL 97-251, -231 and IL 97-226, -254 are superior with respect to nutritional paraflJeters.